JURIDICAL ANALYSIS OF JUDGES' CONSIDERATIONS IN DECIDING CASES FOR REQUESTS FOR DISPENSATION OF MARRIAGE IN THE LEGAL AREA OF THE BANTAENG RELIGIOUS COURT - Aslamiah, Dian; Abbas, Ilham; Husen, Lao De (IBLAM LAW REVIEW, 2023)
This study aims to find out and analyze the implementation of requests for marriage dispensation at the Bantaeng Religious Court. To find out and analyze the factors that influence judges' considerations in deciding cases of marriage dispensation applications in the legal area of ​​the Bantaeng religious court, research, in general, can be classified into two types, namely sociological empirical research (field), namely research conducted with an approach to legal reality in society. This research is based on symptoms in the form of a gap between expectations (das solen) and reality (das sein) in law. Normative research, namely research conducted using an approach to legal norms or substances, legal principles, legal theory, legal arguments, and comparative law. In this study, the authors examined using a qualitative approach as mentioned above in a study. The results showed that the implementation of the application for marriage dispensation at the Bantaeng Religious Court was the Compilation of Islamic Law in Article 53, considering the benefit of the reasons put forward by the applicants and to protect children from early marriage. It is also hoped that the dispensation of the marriage age will benefit the community by providing convenience and solutions for problems. The factors that influence judges' considerations in deciding cases of applications for marriage dispensation in the jurisdiction of the Bantaeng religious court are social conditions, cultural factors, customs, and facts of the trial.